ENGLISH ZONE FOR MOTIVATING STUDENTS TO SPEAK - Oktaviany S, Rurin; Suhartono, Luwandi; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research is to know whether the English Zone in English Language International Course can motivate students to speak English or not. This research was conducted to the students of English Language International Course Pontianak in academic year 2014/2015. Descriptive method was applied in this research. The subjects of this research were the eight students of English for Youth level 3 in speaking class at English Language International Course. The research applied observation technique, as well as indirect communication technique. The tools of collecting data were observation checklist and questionnaire guide. Gardner Attitude/Motivation Test Battery (AMTB) was used as the primary tool of data collection. Based on the observation data, the students motivated to speak. The findings showed that 76.37% students motivated to speak in English zone in the category high. Among to the instrumental motivation, intrinsic motivation, integrative motivation, extrinsic motivation, and resultative motivation, the motivation mostly owned by the students was instrumental motivation which scored 43.21% in the category moderate. The conclusion, English zone can motivate students in English for Youth level 3 of English Language Internasional Course in academic year 2014/2015 to speak. Key words: Motivation, English Zone, Speaking Abstrak: Tujuan penelitian ini adalah untuk mengetahui apakah Zona Bahasa Inggris di English Language International Course dapat memotivasi siswa untuk berbicara atau tidak. Penelitian ini dilakukan terhadap siswa di English Language International Course Pontianak pada tahun akademik 2014/2015. Penelitian ini menggunakan metode deskriptif. Subjek penelitian ini adalah delapan siswa dari English for Youth level 3 di English Language International Course. Penelitian ini menggunakan teknik observasi, serta teknik komunikasi tidak langsung. Alat pengumpulan data adalah observasi checklist dan kuesioner. Gardner Attitude/Motivation Test Battery (AMTB) telah digunakan sebagai alat utama pengumpulan data. Berdasarkan data yang di dapat saat observasi, para siswa termotivasi untuk berbicara. Hasil penelitian menunjukkan bahwa 76,37% siswa termotivasi untuk berbicara dalam zona Bahasa Inggris dalam kategori tinggi. Di antara motivasi instrumental, motivasi intrinsik, motivasi integratif, motivasi ekstrinsik, dan motivasi resultative, sebagian besar yang dimiliki oleh siswa adalah motivasi instrumental yang mencetak 43,21% dalam kategori sedang. Kesimpulannya, zona Bahasa Inggris dapat memotivasi siswa dalam bahasa Inggris untuk English for Youth level 3 dalam English Language International Course pada tahun akademik 2014/2015 untuk berbicara. Kata Kunci: Motivasi, Zona Bahasa Inggris, Berbicara